In vitro slow-growth conservation for two genotypes of Solanum tuberosum L. - Nasiruddin, M; Islam, AKM Rafiul (Bangladesh Journal of Botany, 2018)
To find out the most suitable culture medium formulation to induce slow-growth and reduce the frequency of sub-culturing of the in vitro conserved microplants of the two potato genotypes at 24 ± 1ºC was conducted. Growth was controlled by using different concentrations of sucrose, mannitol, sorbitol (30 g/l) alone or in combination with either mannitol (15, 20 and 25 g/l) or sorbitol (15, 20 and 25 g/l) in murashige and Skoog medium. The results showed that single treatment (Sucrose or mannitol or sorbitol alone) was not feasible for long-term conservation. Combined treatment was responding better and maximum microplant survived (80.82 - 83.15%) after 12 months of storage on (T-8) medium supplemented with 10 g/l sucrose and 20 g/l sorbitol. In this formulation microplants were in very good condition, without phenotypic abnormalities and had enough nodes for sub-culturing up to 12 months. Microplant survival and condition were closely associated with each other but not with root growth.